ARCHITECTURAL INFLUENCES OF ISTANA LAMA SERI MENANTI, NEGERI SEMBILAN - Zainal Abidin, Nurdiyana; Raja Shahminan, Raja Nafida; Ibrahim, Fawazul Khair (PLANNING MALAYSIA, 2017)
Traditional Malay Royal Palaces in Malaysia are monumental buildings representing the rich architecture, heritage, traditions and expertise of the Malays. The architecture of these palaces differs from one another to demonstrate the identities of the vernacular architecture as timber palaces were representations of Traditional Malay Houses on an exaggerated scale. One example of this is Istana Lama Seri Menanti in Kuala Pilah which is a four-storey timber palace built in the 20th century by Malay carving experts. Another factor to consider is the rich cultural acceptance of the Minangkabau as they have been around in Negeri Sembilan since the 15th Century. Hence, this paper aims to determine the architectural identity of Istana Lama Seri Menanti through the influences on the palace architecture and the factors affecting these influences. The research methods undertaken include case studies, interviews with experts, and document and historical analysis of subjects about palaces. The findings conclude that the key element of ‘atap bergonjong’ cannot be found in Istana Lama Seri Menanti which has the more common modest curve of the roof ridges found in houses of Negeri Sembilan. Furthermore, Chinese influences on the woodcarvings of the palace can be seen on the columns and beams of the exterior of the palace. In conclusion, there are many influences on the architectural identity of Istana Lama Seri Menanti such as Chinese influences and British’s political influences on the design of the palace.